Evidence for associations between traffic calming and safety and active transport or obesity: A scoping review. (December 2017) - Brown, V.; Moodie, M.; Carter, R.
Abstract: Traffic calming interventions are policy relevant measures that aim to improve the safety of motorists, passengers, pedestrians and cyclists by reducing the frequency and severity of traffic accidents. Limited evidence exists on secondary effects of investment in traffic calming and safety, including effects on rates of transport-related physical activity (active transport) and more distal outcomes such as obesity. This study aims to review evidence for association between traffic calming and safety and transport-related physical activity or obesity. A systematic search of the peer-reviewed literature was undertaken, with narrative review and quality assessment of evidence from 71 studies (12 reporting associations with obesity, 59 reporting associations with active transport). Our review demonstrates that whilst a feasible logic pathway exists between traffic calming and active transport and obesity, the current state of the evidence is inconclusive. The quality of evidence is also relatively low, particularly given the challenges involved in collecting rigorous evidence of environmental-type interventions. Whilst the evidence for net positive health benefits of active transport is well established, the challenge now is to progress from health impact assessment to evaluation of specific interventions that increase active transport. Significant scope exists for a more thorough understanding of the impacts of traffic calming and safety on secondary health outcomes, taking advantage of natural experimental opportunities and using validated and rigorous measures of exposure and outcomes. A more complete understanding of the secondary effects of traffic calming and safety would allow for full economic evaluation of traffic calming interventions to be conducted, incorporating wider health benefits. This information would prove invaluable at the policy level, as incremental micro-scale interventions such as traffic calming are generally feasible and affordable. This information would also inform the more systemic change required to reverse the obesity and physical inactivity epidemics and to improve the health of populations. Highlights: A feasible logic pathway exists between traffic safety, active transport and obesity. Yet limited evidence exists for secondary effects of traffic calming interventions. Net health benefits of active transport are now well-established. More information is now required on specific ways to improve rates of active transport.